Effect of Soil Washing on Petroleum-Hydrocarbon Distribution on Sand Surfaces - A. Bhandari; J. T. Novak; D. C. Dove (Journal of Hazardous Substance Research, 1999)
A soil washing study was performed to evaluate the treatability of New River sand contaminated in the laboratory with a petroleum distillate. Unaltered and base-extracted sands were mixed with petroleum hydrocarbons, equilibrated, and washed with water or a surfactant at two different pH values (7 and 12). The surfactant had no significant effect on contaminant removal efficiencies at neutral pH. Treatment efficiencies of baseextracted sand particles were 10 to 13% higher than for the unaltered sands. Scanning electron microscopy (SEM) with elemental X-ray microprobe was used to determine the distribution of iron and carbon on the New River sand surface. Qualitative interpretations of the SEM/X-ray photomicrographs disclosed that iron oxides were associated with organic carbon on the sand surfaces, with sulfur believed to be a constituent of the petroleum contamination. Low petroleum removal efficiencies for New River sand observed in previous studies were believed to be influenced by the high iron oxide content of the sand and the affinity of these metal oxides to bind natural and petroleum-derived organic carbon.
Keywords: soil washing; petroleum hydrocarbons; surfactant; humic acids; SEM